Satisfaction on hostel furniture in UiTM Jengka / Siti Ainin Suhail Mohd Osni - Mohd Osni, Siti Ainin Suhail (2014)
Satisfaction will be achieved when outcome meet the expectation. (Kotler et al., 2006 Ergonomic in simple term can be defined as the study of interaction between human beings and the objects they use and the environments in which they function. The aim of this study is to relate the factors that contribute to the satisfaction of students toward hostel furniture in UiTM Jengka Pahang. Total 400 questionnaires were distributed to students in UiTM Jengka with 100 questionnaire to each college. The data were gathered and analyzed using SPSS system. This research help to identify the unrecorded complains from the students regarding hostel furniture problem. The result of this study can be useful as future reference regarding research on hostel furniture. The result from the survey can be used to create better ergonomic design of hostel furniture.